Basics: vegetables : techniques, tips, and 70+ recipes to confidently cook with vegetables - Augé, Séverine (Hardie Grant Books America, 2025)
"Basics: Vegetables is the first in a series that will completelydemystify cooking through step-by-step photography and clear instruction. It is a short but comprehensive photographic primer with recipes and techniques that showcase both classic vegetarian dishes and modern reinventions. Whether you're having a vegetarian guest over for dinner, trying to make a weekday lifestyle shift, or years into avegetarian diet, learn (or relearn) the basics with step-by-step photos and easy-to-follow instructions. From Hasselback Butternut Squash to Risotto Verde or Tomato Tatin, your next vegetarian meal--or dinner party--is only a few ingredients away. Make spinach-tinted green waffles with eggs on the weekend, or treat yourself to a hearty lentil shepherd's pie, assembled in 15 minutes and perfect for weekday lunch leftovers. Basics: Vegetables has 80 recipes for vegetarian and vegetarian-aspiring cooks ready to grow their repertoire of delicious vegetable-forward meals. It is a must-have addition to any cookbook library."--